Analisis Etnosemantik Tuturan Verbal dan Tindakan Nonverbal Tradisi Gehan Tena pada Masyarakat Lewoawang - Leba, Bartoldus Sora; Mare, Fransiska Jone; Lein, Natalia Onie (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the lexical and grammatical meanings of verbal speech and nonverbal actions in the Gehan Tena tradition and find the local cultural values reflected in these speech and actions. This research uses an ethnosemantic approach, which combines the analysis of the meaning of language (semantics) with the cultural context of the speakers (ethnolinguistic). The method used is qualitative descriptive with data collection techniques in the form of participatory observation, interviews, and documentation. The data is analyzed in three stages, namely data reduction, data display, and conclusion-making. The results of the study showed that (1) verbal speech and nonverbal actions are closely related to each other. Speech is followed by action or vice versa; (2) The lexical meaning of speech and action is obtained from the analysis of each speech word and action. Not all words have a lexical meaning in the form of words, but they are also in the form of phrases; (3) grammatical meaning is obtained from the analysis of spoken language units and actions in the form of phrases and sentences; (4) the lexical and grammatical meaning of speech and actions becomes the basis for the interpretation of local cultural values; (5) local cultural values of every speech and action related to the relationship between humans and God, others and the created nature.